An analysis and evaluation of the annual library conferences of the Thai Library Association as perceived by members, 1973-1982 - Chutima Sacchanand; Vallejo, Rosa M.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1984)
The study analyzed and evaluated annual library conferences conducted by the Thai Library Association from 1973 to 1982. Tools and techniques used in the survey method were documentary analysis, questionnaire, and interviews. A questionnaire was sent to 303 TLA members who were chosen by stratified random sampling from a population of 605; 260 responded.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library Associations--Thailand.; Library science--Thailand--Congresses.; Thai Library Association